Development Strategies for Micro, Small, and Medium Enterprises (MSMEs) Enhancing the Income of Tempe Chips Enterprises - Budi Setiawan; Zaenal Abidin; Pini Susanti; Sayida Khoiratun Nisak; Hasna Dewi (Zabags International Journal of Engagement, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting local economic growth, yet they often face challenges related to limited capital, weak innovation, poor management, and restricted market access. This study aims to analyze the development conditions of MSMEs in tempe chips enterprises in Mendahara Ilir Village and to formulate effective strategies for increasing business income. The research employs a qualitative case study approach, utilizing observation, in-depth interviews, and documentation involving business owners, workers, consumers, and village officials. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, with source, technique, and time triangulation to ensure validity. The findings reveal that tempe chips enterprises encounter significant obstacles, including capital constraints, lack of product innovation, weak managerial practices, limited use of digital technology, and narrow marketing networks. Nevertheless, some efforts have been initiated, such as improving packaging, introducing new flavors, and using social media for promotion, though these remain underdeveloped. The study contributes theoretically by integrating the resource-based view and Schumpeterian innovation theory within the rural MSME context, while practically offering applicable recommendations for entrepreneurs and local government in designing empowerment policies. The implications highlight the necessity of a holistic approach to MSME development based on local potential to enhance competitiveness and community welfare.